A Refugee Rose of competencies and capabilities for mental healthcare of refugees. Issue 2 (14th March 2022) - Bhui, Kamaldeep
Abstract : In this paper, I set out the challenges of care for refugees and suggest approaches to assessment and intervention. I discuss clinical interventions that can address the immediate concern of the clinician in a bio-psycho-social framework, and the value of considering eco-social and structural influences that can hinder recovery and perpetuate inequalities. Refugees face multiple adversities before, during and after escaping from life-threatening situations, political violence, torture and persecution. They present with complex health needs and encounter hostility from host countries and public services, which see their needs as an additional demand on the public purse. Regrettably, existing care practice and training of professionals do not often include skills for working across cultures, including cultural formulations and fair assessment, cultural adaptation of interventions, cultural competence and cultural consultation methods, including clinical ethnography and exploration of cultural identity and explanatory models. There are little data on effective and kind models of interpretation and translation. Care systems are rarely designed to fully address the needs of refugees. Health practitioners are not trained to address structural and institutional racism and discrimination, which leads to exclusion of the most marginalised, with little attention to social justice and fair processes as part of appropriate healthcare.